The weakest link: competence and prestige as constraints to referral by isolated nurses in rural Niger - Van Lerberghe Wim; Bossyns Paul (BMC, 2004)
Abstract Background For a health district to function referral from health centres to district hospitals is critical. In many developing countries referral systems perform well below expectations. Niger is not an exception in this matter. Beyond obvious problems of cost and access this study shows to what extent the behaviour of the health worker in its interaction with the patient can be a barrier of its own. Methods Information was triangulated from three sources in two rural districts in Niger: first, 46 semi-structured interviews with health centre nurses; second, 42 focus group discussions with an average of 12 participants - patients, relatives of patients and others; third, 231 semi-structured interviews with referred patients. Results Passive patients without 'voice' reinforce authoritarian attitudes of health centre staff. The latter appear reluctant to refer because they see little added value in referral and fear loss of power and prestige. As a result staff communicates poorly and show little eagerness to convince reluctant patients and families to accept referral proposals. Conclusions Diminishing referral costs and distance barriers is not enough to correct failing referral systems. There is also a need for investment in district hospitals to make referrals visibly worthwhile and for professional upgrading of the human resources at the first contact level, so as to allow for more effective referral patterns.